Quantitative pre-clinical screening of therapeutics for joint diseases using contrast enhanced micro-computed tomography. Issue 9 (September 2016) - Willett, N.J.; Thote, T.; Hart, M.; Moran, S.; Guldberg, R.E.; Kamath, R.V.
Summary: Objective: The development of effective therapies for cartilage protection has been limited by a lack of efficient quantitative cartilage imaging modalities in pre-clinical in vivo models. Our objectives were two-fold: first, to validate a new contrast-enhanced 3D imaging analysis technique, equilibrium partitioning of an ionic contrast agent-micro computed tomography (EPIC-μCT), in a rat medial meniscal transection (MMT) osteoarthritis (OA) model; and second, to quantitatively assess the sensitivity of EPIC-μCT to detect the effects of matrix metalloproteinase inhibitor (MMPi) therapy on cartilage degeneration. Methods: Rats underwent MMT surgery and tissues were harvested at 1, 2, and 3 weeks post-surgery or rats received an MMPi or vehicle treatment and tissues harvested 3 weeks post-surgery. Parameters of disease progression were evaluated using histopathology and EPIC-μCT. Correlations and power analyses were performed to compare the techniques. Results: EPIC-μCT was shown to provide simultaneous 3D quantification of multiple parameters, including cartilage degeneration and osteophyte formation. In MMT animals treated with MMPi, OA progression was attenuated, as measured by 3D parameters such as lesion volume and osteophyte size. A post-hoc power analysis showed that 3D parameters for EPIC-μCT were more sensitive than 2D parameters requiring fewer animals to detect a therapeutic effect of MMPi. 2D parameters were comparable between EPIC-μCT and histopathology. Conclusion: This study demonstrated that EPIC-μCT has high sensitivity to provide 3D structural and compositional measurements of cartilage and bone in the joint. EPIC-μCT can be used in combination with histology to provide a comprehensive analysis to screen new potential therapies.